2004
DOI: 10.1016/j.jacc.2003.09.066
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of ejection intraventricular pressure gradients

Abstract: For the first time, ejection IVPGs can be accurately visualized and measured by Doppler-echocardiography. Important aspects of the dynamic interaction among myocardial performance, load mechanics, and ejection dynamics can be assessed in the clinical setting using this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 26 publications
3
53
0
1
Order By: Relevance
“…11 We have recently developed and validated a new method to obtain noninvasive measurements of EIVPDs by postprocessing color Doppler M-mode (CDMM) echocardiograms. 12,13 The present study was designed to study the utility of EIVPD as a noninvasive index of systolic chamber function in vivo with a high-fidelity pressure and conductance instrumentation animal setup. The specific objectives were (1) to correlate Doppler-derived EIVPDs with invasive reference indices of systolic function in a range of inotropic states induced by pharmacological interventions and acute ischemic cardiomyopathy (study 1), (2) to assess the modification of EIVPDs caused by acute load changes (study 2), and (3) to assess the potential error caused by scan line misalignment on the estimation of EIVPDs (study 3).…”
Section: See P 1684mentioning
confidence: 99%
See 1 more Smart Citation
“…11 We have recently developed and validated a new method to obtain noninvasive measurements of EIVPDs by postprocessing color Doppler M-mode (CDMM) echocardiograms. 12,13 The present study was designed to study the utility of EIVPD as a noninvasive index of systolic chamber function in vivo with a high-fidelity pressure and conductance instrumentation animal setup. The specific objectives were (1) to correlate Doppler-derived EIVPDs with invasive reference indices of systolic function in a range of inotropic states induced by pharmacological interventions and acute ischemic cardiomyopathy (study 1), (2) to assess the modification of EIVPDs caused by acute load changes (study 2), and (3) to assess the potential error caused by scan line misalignment on the estimation of EIVPDs (study 3).…”
Section: See P 1684mentioning
confidence: 99%
“…CDMM images were obtained from 5-chamber views as described. 13 The method used for digital image processing to obtain EIVPDs has been reported 12 and validated elsewhere. 13 Other authors have also demonstrated the accuracy of a similar approach to measure intraventricular pressure differences in diastole and its applicability in the clinical setting.…”
Section: Echocardiographic Image Acquisition and Analysismentioning
confidence: 99%
“…Recently, the possibility of measuring intracardiac pressure gradients by digital processing of color Doppler M-mode images has been developed by our [11][12][13][14] and other groups. 15,16 We hypothesized that this method also could be suitable for measuring the RVFPD in clinical practice.…”
Section: Clinical Perspective P 1023mentioning
confidence: 99%
“…[11][12][13] Briefly, if the M-mode cursor closely approximates a flow streamline, the spatiotemporal velocity distribution of a discrete blood sample is provided by the value of its corresponding pixel color: v(s,t), where v represents velocity, s represents the linear dimension of the streamline, and t is time. Thus, the color M-mode Doppler recording provides the data necessary to solve Euler's momentum equation:…”
Section: Echocardiographic Image Acquisition and Analysismentioning
confidence: 99%
“…To measure them requires simultaneous high-fidelity pressure measurements with multiple micromanometer catheters placed invasively within the heart, a highly demanding task technically and entirely inappropriate for clinical use. Fortunately, Yotti et al have applied fluid dynamics principles to measure noninvasively ejection intraventricular pressure differences (EIVPD) from color M-mode Doppler data, 1,6 extending concepts originally developed for diastolic IVPG by Thomas, Greenberg, and others from the Cleveland Clinic. 7,8 To understand how we can measure pressure gradients from velocity data, we start with the "almost" complete Bernoulli equation with both inertial and convective terms (we still omit the viscous term because it is negligible in almost every intracardiac situation):…”
Section: See P 1771mentioning
confidence: 99%